Innovations-led Farming is the Way Forward for Resilience, Sustainability and Improved Livelihood in Indian Arid Zone: OPINION PAPER - O P Yadav (Annals of Arid Zone, 2025)
Arid regions are unique agricultural production and ecological systems characterized by challenging agro-climatic conditions and stressful environments for crops and livestock putting a ceiling on agricultural productivity.The inherent vulnerability of farming to stress conditions is further accentuated by climate change. This situation calls for improving productivity and strengthening resilience of farming to provide sustainable livelihoods for farming communities. This article highlights role of technological innovations to achieve this daunting task. Greater productivity, resilience, sustainability, and improved livelihood require not only multiple technological interventions but would also necessitate proper policy. Role of integrated farming, resilient crops and climate-smart livestock management are very vital in improving productivity and resilience of agricultural system. On the other hand, innovations in water management, sustaining soil health, precision agriculture, nature-friendly farming and use of digital tools will form foundation of enhanced sustainability. Engaging farmers in designing and testing of new technologies, delivering improved technologies at his doorsteps and enhancing their entrepreneurship skills, both at individual and community levels, hold the key to further enhance rural livelihood. While doing so, it is important to keep a constant and careful watch on changes occurring in the state of natural resources to ensure that there is no infidelity with combating desertification in agricultural lands